Pengaruh Pemberian Plant Growth Promoting Rhizobacteria (PGPR) Asal Akar Tanaman Bambu Terhadap Pertumbuhan Kecambah Padi: Effect of Plant Growth Promoting Rhizobacteria (PGPR) Bamboo Roots on Rice Sprout Growth - Hamdayanty Hamdayanty; Asman; Kiki Widya Sari; Sal Sabila Attahira (Jurnal Ecosolum, 2022)
Rice (Oryza sativa) is one of the food commodities that have an important role that is used as a staple food for most of the world's population, especially in Indonesia. Plant Growth Promoting Rhizobacteria (PGPR) is one of the bioorganic fertilizer that can be used to stimulate plant growth. The purpose of this study was to examine the effectiveness of PGPR to support seed germination. The first step is to make PGRP from bamboo roots with 3 methods. PGPR was then tested to see the germination of rice seeds through the rolled paper test method. The provision of PGPR has little effect on the length of the root length of rice sprouts. The root length of the PGPR treatment is 10.68 cm while the control is 10.45 cm. This shows that the PGPR treatment has a fairly good impact on the development of sprouted rice roots. PGPR treatment has an effect on the wet and dry weight of roots and shoots of rice sprouts. The average wet and dry weight of the PGPR treatment were higher than the control treatment. PGPR is recommended to be given to obtain rice yields to obtain better quality and quantity of rice plants.